Community Service (Pkm) Efforts to Improve Soft Skills among Youth in Seminyak Village, Badung Regency - Sugiantiningsih, Anak Agung Putu; Yasa, I Gede Putu; Suyasa, I Made; Wirantini, Ni Kadek Ayu (Abdi Masyarakat, 2023)
The aim of this research is to determine efforts to improve soft skills among youth in facing the world of work in Seminyak Subdistrict, Badung Regency, and how to overcome obstacles in improving soft skills among youth in Seminyak Subdistrict, Badung Regency to face the world of work. This research uses qualitative research, with the research location in Seminyak sub-district, Badung district. The type of instrument used is a non-test instrument in the form of; interview guide and documentation. The data analysis technique goes through the stages of data reduction, data presentation, and drawing conclusions. The results of the research are expected to show that efforts to improve soft skills among young people in facing the world of work in Seminyak sub-district, Badung district, Seminyak sub-district, Badung regency have not been optimal, however there have been efforts made such as holding training, improving, developing and determining training themes to attract attention among young people to take part in soft skills training. The obstacles faced in efforts to improve soft skills among youth are from the youth themselves, namely; lack of participation, awareness and discipline from the organizers, namely; lack of socialization, infrastructure, funding, and limited time. Based on the observations made by the author, the author will create it in the form of Community Service (PKM) activities. To help improve soft skills among youth, with the expected output in the form of training and reputable nationally indexed journals.